LOS VINOS DEL VALLE DE GUADALUPE: ANÁLISIS DE SU COMERCIALIZACIÓN - López, Virginia; Sotelo, Carla (European Scientific Journal, ESJ, 2014)
Wine marketing has become a subject of controversy due to social and economic weight has been given to this drink. The wines produced in the Valle de Guadalupe, BC are marketed mostly in this area or surrounding areas (Ensenada, Mexicali y Tecate, B.C) another partr of the production is going toward the center of the country. Regarding export these are minimal